The Role of KOCCA (Korea Creative Content Agency) as been Implemented in the Spread of South Korea Culture by the Means of the Creative Industry : chapter II development of the creative industry in south korea and potential of KOCCA (Korea Creative Industri Agency) - Siswanto, Fadillah nisrina; Amalia, Novi Rizka (Mediasi Journal of International Relations, 2024)
The influence of the Korean wave has influenced the world and created quite a big influence on the international market, looking at the large impact that Korean has had In this wave , the government formed an institution that supports the spread of culture, especially in the creative industry sector, namely KOCCA. KOCCA is a government institution that is directly responsible for the growth of South Korea's creative industry as well as regulating South Korean content so that it is in line with the South Korean cultural values it wishes to convey. This research aims to analyze KOCCA's role in expanding the spread of South Korean culture through the creative industry. The method used in this research is a qualitative method with bibliography data collection techniques. This research examines KOCCA's role in expanding the spread of South Korean culture through the creative industry. The concepts used in this research are the concept of soft diplomacy and multitrack diplomacy track one and track two . The results of the research show that KOCCA's role in spreading South Korea's creative industry is as a liaison between the government and society and the international community, as a promotional and supporting forum for the creative industry, as a supporter of South Korea's positive image in the eyes of the world.